2016
DOI: 10.1016/j.jvoice.2015.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Breathy Voice Quality Using Pitch-strength Estimates

Abstract: Background The characteristic voice quality of a speaker conveys important linguistic, paralinguistic and vocal health related information. Pitch strength refers to the salience of pitch sensation in a sound and was recently reported to be strongly correlated with the magnitude of perceived breathiness based on a small number of voice stimuli. Objective The current study examined the relationship between perceptual judgments of breathiness and computational estimates of pitch strength based on the Aud-SWIPE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…We were also concerned that the individual differences in the degree of nasality might affect the measure instead of breathiness, so we decided not to include H1-H2 in our study. 2 An acoustic estimate of pitch strength is also known to capture signal periodicity and predict perceived breathiness (Eddins, Anand, Camacho, & Shrivastav, 2016). Pitch strength refers to the degree to which listeners can perceive pitch in a sound, and this perceptual measure has also shown a strong correlation with perceived breathiness (Shrivastav, Eddins, & Anand, 2012); however, pitch strength is not commonly used as an acoustic correlate of breathiness and was not included in this study.…”
Section: Estimates Of Breathinessmentioning
confidence: 99%
“…We were also concerned that the individual differences in the degree of nasality might affect the measure instead of breathiness, so we decided not to include H1-H2 in our study. 2 An acoustic estimate of pitch strength is also known to capture signal periodicity and predict perceived breathiness (Eddins, Anand, Camacho, & Shrivastav, 2016). Pitch strength refers to the degree to which listeners can perceive pitch in a sound, and this perceptual measure has also shown a strong correlation with perceived breathiness (Shrivastav, Eddins, & Anand, 2012); however, pitch strength is not commonly used as an acoustic correlate of breathiness and was not included in this study.…”
Section: Estimates Of Breathinessmentioning
confidence: 99%
“…To overcome the requirement of synthetic speech, we have also considered an index known as pitch strength to evaluate dysphonia in natural and synthetic speech (13,46). Borrowing from studies of the tonality conveyed by non-speech stimuli (47), samples from dysphonic voices were evaluated in a series of perceptual studies and modeled using computational methods for pitch strength (i.e., pitch salience from weak to strong).…”
Section: Psychoacoustic Approach To the Study Of Voice Qualitymentioning
confidence: 99%
“…Borrowing from studies of the tonality conveyed by non-speech stimuli (47), samples from dysphonic voices were evaluated in a series of perceptual studies and modeled using computational methods for pitch strength (i.e., pitch salience from weak to strong). Shrivastav et al (2012) reported a strong negative correlation (r = −0.989) between pitch strength judgments and loudness ratio, while Eddins et al (2016) demonstrated that computational pitch strength estimates were strongly and negatively correlated with perceived breathiness. These studies show that pitch strength or pitch salience is low for breathy voices and pitch strength increases as the vocal breathiness decreases.…”
Section: Psychoacoustic Approach To the Study Of Voice Qualitymentioning
confidence: 99%
See 2 more Smart Citations